tDCS of the Cerebellum: Where Do We Stand in 2016? Technical Issues and Critical Review of the Literature - van Dun, Kim; Bodranghien, Florian C. A. A.; Mariën, Peter; Manto, Mario U. (Frontiers in Human Neuroscience, 2016)
Transcranial Direct Current Stimulation (tDCS) is an up-and-coming electrical neurostimulation technique increasingly used both in healthy subjects and in selected groups of patients. Due to the high density of neurons in the cerebellum, its peculiar anatomical organization with the cortex lying superficially below the skull and its diffuse connections with motor and associative areas of the cerebrum, the cerebellum is becoming a major target for neuromodulation of the cerebellocerebral networks. We discuss the recent studies based on cerebellar tDCS with a focus on the numerous technical and open issues which remain to be solved. Our current knowledge of the physiological impacts of tDCS on cerebellar circuitry is criticized. We provide a comparison with transcranial Alternating Current Stimulation (tACS), another promising transcranial electrical neurostimulation technique. Although both tDCS and tACS are becoming established techniques to modulate the cerebellocerebral networks, it is surprising that their impacts on cerebellar disorders remains unclear. A major reason is that the literature lacks large trials with a double-blind, sham-controlled and cross-over experimental design in cerebellar patients.